(untitled) (Colombia Medica, 2016)
To better guide science and technology policies, it is required high quality and updated information on organizations, researchers, projects and products. The growth of the Internet use in research has provided more information on these aspects; however, the volume of data made more difficult the methods for processing and organizing them in a way useful to understand and make informed decisions. Problems such as duplication of information, difficulties in monitoring processes (authors and projects with products), and the lack of identification of thematic research and knowledge networks have increased in the last twenty years. In all this, the most important factor hindering the organization of data has been the need to identify each component.